Third cranial nerve palsy in an 88-year-old man after SARS-CoV-2 mRNA vaccination: change of injection site and type of vaccine resulted in an uneventful second dose with humoral immune response. Issue 2 (8th February 2022) - Cicalese, Maria Pia; Ferrua, Francesca; Barzaghi, Federica; Cerri, Federica; Moro, Matteo; Aiuti, Alessandro; Silvani, Paolo
Abstract : Vaccines for SARS-CoV-2 currently authorised by the European Medicine Agency are effective, safe and well tolerated in practice. Awareness of rare potential vaccine-related adverse effects (AEs) is important to improve their recognition, management and reporting. An 88-year-old man attended the emergency department with incomplete palsy of the right third cranial nerve 3 days after the first administration of Moderna mRNA-1273 SARS-CoV-2 vaccine. Imaging ruled out a vascular accident and a vaccine AE was hypothesised. Two weeks of oral steroids led to the patient's recovery, but without evidence of humoral immune response to vaccine. Thus, full immunisation with a dose of Pfizer mRNA-BNT162b2 SARS-CoV-2 vaccine in a different site was attempted. This was uneventful and followed by a robust antibody response. Empirical change of site and vaccine brand may represent a tailored option to obtain full immune protection in selected patients, after vaccine AEs.